Research on the Influence of Tolerance of Opportunistic Behaviors of Channel Boundaries on the Choice of Response Strategies - Chen, Jinsong; Liu, Zhaoxia; Hu, Ruoqian (Frontiers in Psychology, 2022)
In the Chinese society, border agents in channel transactions will choose different opportunistic behavior response strategies to the tolerance of other members based on the relationship between the two parties. Based on 206 valid questionnaires collected, structural equation model and regression analysis were used to investigate the influence of opportunistic behavior tolerance on response strategy selection. The results show that the channel boundary personnel's tolerance to opportunistic behavior (based on work or personal) negatively influences their choice of a positive response strategy and positively influences their choice of a negative response strategy. Among the mediating effects of contract formulation, transaction terms have a positive effect on the choice of negative response strategies based on the work and individual opportunistic behavior tolerance and have no mediating effect on the choice of positive response strategies; the contingency clause has no mediating effect on the choice of positive response strategies based on individual opportunistic behavior tolerance.